Identification of the Geobacter metallireducens BamVW Two-Component System, Involved in Transcriptional Regulation of Aromatic Degradation - Juárez, Javier F. (American Society for Microbiology (ASM), 2010)
Regulation of aromatic degradation in obligate anaerobes was studied in the Fe(III)-respiring model organism Geobacter metallireducens GS-15. A two-component system and a σ(54)-dependent promoter were identified that are both involved in the regulation of the gene coding for benzoate-coenzyme A ligase, catalyzing the initial step of benzoate degradation.